Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex] 4b\cdot3b-2b=102\\
12b^2-2b-102=0\\
6b^2-b-51=0\\
6b^2+17b-18b-51=0\\
b(6b+17)-3(6b+17)=0\\
(b-3)(6b+17)=0\\\
b=3 \vee b=-\frac{17}{6}[/tex]
4b×3b-2b=102
12b^2 - 2b = 102
12b^2 - 2b - 102 = 0
divide by 2
6b^2 - b - 51
(6b + 17)(b - 3) = 0
6b + 17 = 0
6b = -17
b = -17/6 or 2 5/6
b - 3 = 0
b = 3
12b^2 - 2b = 102
12b^2 - 2b - 102 = 0
divide by 2
6b^2 - b - 51
(6b + 17)(b - 3) = 0
6b + 17 = 0
6b = -17
b = -17/6 or 2 5/6
b - 3 = 0
b = 3
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.